Improving the trustworthiness, usefulness, and ethics of biomedical research through an innovative and comprehensive institutional initiative - Strech, Daniel; Weissgerber, Tracey; Dirnagl, Ulrich; on behalf of QUEST Group (PLOS Biology, 2020)
This Community Page article describes an ongoing large-scale structured initiative at the Berlin Institute of Health which aims at improving the robustness, reproducibility and transparency of research in an academic biomedical setting.